PERSEPSI MASYARAKAT TERHADAP PROGRAM KETAHANAN PANGAN DI KECAMATAN RIMBO BUJANG KABUPATEN TEBO - Anhar Ahmadi, M.; Suandi, Suandi; HD, Ernawati (Penerbit Lafadz Jaya, 2024)
This research is aimed at: 1) to describe the implementation and performance achievements of the food security program in Rimbo Bujang District, Tebo Regency, 2) to determine the relationship between community perceptions and the implementation of the food security program in Rimbo Bujang District, Tebo Regency. The data used is primary data and secondary data. The data analysis method used is descriptive analysis and the bivariate Pearson correlation test. This research was carried out in Rimbo Bujang District. The number of samples in this study was 85 people registered in the group. From the research results, it can be seen that (1) The implementation of the food security program implemented in Rimbo Bujang District has gone well and is in accordance with applicable technical instructions, (2) Of the six criteria for public perception, namely effectiveness, efficiency, adequacy, equity, responsiveness and accuracy. There is one indicator that is an inhibiting factor in the implementation of food security programs, namely the effectiveness indicator, (3) The results of the bivariate Pearson correlation analysis show that there are four public perceptions, namely adequacy, equity, responsiveness and accuracy, which correlate significantly with the food security program (preparation stage) budgeting stage and implementation stage) by looking at the significance value of Sig. (2-tailed) < 0.05.